Magnitude of Carbaryl Residues in and on Castor - Singh, K P; Pandey, S Y; Galhotra, R (Annals of Arid Zone, 2016)
A field trial was conducted to study the extent of carbaryl residues in and on castor. The crop was treated with Sevin 50% wettable powder, Sevimol-40 LV and Sevin 10% dust @ 0.75 to 3.0 kg ai/ha, thrice at an interval of 15 days, at flowering. Seed and straw samples were drawn 12 days and 20Â·days, after the last application. Samples were analysed colorimetrical’y. Carbaryl residues in and on seed were non-detectable, while straw samples showed residues varying from 2.21 to BDL. The carbaryl residue detect d was far below the tolerance limit of 100.0 ppm prescribed by WHO/FAO for fodder and forage.